Prescription/Non-prescription Medicine Misuse and Regulation – Time for a Modern, Fit for Purpose Approach - Wazaify, Mayyada; Scott, Jenny (Journal of Pharmacy Practice and Community Medicine)
Considering the breadth of medicines available without a prescription and the spectrum of problems that can arise with medication use, pharmacists, particularly those working in community pharmacies, have the potential to make a huge impact on society. Pharmacy like other health professions, has its own codes of ethics for practice, often focused at individual country level. The ownership of such codes is very often internal (where professional bodies regulate their own ethics)e.g. Jordan, but may also be external (where statutory bodies regulate professions) e.g. UK. Such enforced codes of practice must be followed, not only to safeguard the patient and public but also to preserve the integrity of the profession. Nevertheless, violations in practice and ethical standards do happen for many reasons.